Utilization of mobile web application for restaurant food ordering with delivery tracking status - Norhayati Daut; Jetol Bolongkikit; Asni Tahir; King, Lieng Lau; Aslina Baharum; Hui, Keng Lau; Norazlina Khamis (Pusat e-pembelajaran, UMS, 2022)
Been relying on either pen and paper or call-in orders, which is inefficient, error-prone, time-consuming, and labour-intensive. Handwritten orders leave a lot of room for potential human errors. Taking the wrong orders or the staff’s poor handwriting, for example, may create confusion in the kitchen, lead to food and labour wastage, and increase the unnecessary budget. There are some native apps developed to tackle these issues on both Android and iOS platforms. These apps merely transform the practice from a paper-based ordering system to an online ordering system, which improves and refines customers’ experiences when they place orders. However, the process of developing apps that support multiple platforms is complex, laborious, and expensive. This paper showcases the use of a mobile web application, equipped with tracking status to allow a customer to place an online order, check the order status, and track the delivery. To develop the system, the combination of Agile and Waterfall models was used. The System Usability Scale (SUS) was used to test the usability of this mobile web application. The mobile web app can help restaurant owners switch to an online ordering system by adding their interactive online menu to the app, integrating payments, and organizing delivery, while the customers can browse through the menu, place online orders, and track the deliveries